Case Report: Primary extraskeletal osteosarcoma in prostate - Xu, Youli; Chen, Xing (Frontiers in Oncology, 2025)
Extraskeletal osteosarcoma (EOS) is an extremely uncommon malignant soft tissue sarcoma that carries a poor prognosis. However, EOS occurring in the prostate is especially rare. The purpose of this case report is to present the radiological features and immunohistochemistry results of the neoplasm in a 72-year-old man. In the case, contrast-enhanced CT and contrast-enhanced MRI clearly showed the primary lesion and the surrounding soft tissue invasion. In our case, massive calcification was seen within the tumor. Despite being regarded as a significant imaging symptom of EOS, calcification only happens in about half of the cases. In our case, positive immunohistochemistry results were included as follows: SATB2 (+), SMA (+), CD99 (+), CK (focal +), Ki-67 (+, hot spots about 40%), P63 (focal +), and Vim (+). Extensive resection is the preferred treatment method for localized lesions. Further adjuvant radiotherapy significantly decreased local recurrences, but chemotherapy did not decrease the risk of systemic recurrence.